2011
DOI: 10.1371/journal.pone.0024817
|View full text |Cite
|
Sign up to set email alerts
|

Incident Dementia in a Defined Older Chinese Population

Abstract: BackgroundCurrent knowledge about incident dementia is mainly derived from studies undertaken in the West, showing that dementia is related to older age, low socio-economic status, lack of social network, depression and cardiovascular disease risk factors. We know little about incidence and predictors of dementia in China, where the prevalence is increasing and the patterns of risk factors are different.MethodsUsing a standard interview method, we examined 1526 non-demented people aged ≥65 years who had at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 30 publications
2
68
1
7
Order By: Relevance
“…In order to study the effect of ARBs on AD, we excluded subjects with dementia or any diagnosis of apparent cerebrovascular disease before the start of antihypertensive treatment. In addition to the negative finding regarding ARB use and AD risk reduction, our data showed that traditional risk factors for dementia, such as age, DM, and female sex, 29 are also independent factors for the incidence of AD, supporting that our data are solid. However, antihypertensive regimens other than ARBs were not equally distributed in the 2 groups.…”
Section: Discussionsupporting
confidence: 78%
“…In order to study the effect of ARBs on AD, we excluded subjects with dementia or any diagnosis of apparent cerebrovascular disease before the start of antihypertensive treatment. In addition to the negative finding regarding ARB use and AD risk reduction, our data showed that traditional risk factors for dementia, such as age, DM, and female sex, 29 are also independent factors for the incidence of AD, supporting that our data are solid. However, antihypertensive regimens other than ARBs were not equally distributed in the 2 groups.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, we have examined a populationbased cohort study in China, and found that compared with never smokers, current smokers at baseline had a substantial excess in incident dementia (i.e., multivariate adjusted odds ratio was 2.39 [1.21-4.72]). Former smokers were also found to have an increase in the risk, but not significantly (OR: 1.66; 95% CI: 0.53-5.16) [12], which is consistent with the findings reported in the review by Anstey et al probably suggesting that giving up smoking would reduce the risk of dementia [8]. This provides further confirmation of the dangers that smoking poses to dementia risk.…”
supporting
confidence: 88%
“…In Austria, Arrich et al 19 found that occupation and income have an independent effect on risk of death, which is sustained after adjusting for stroke severity. Analyzing the Anhui cohort data 20 and systematically reviewing literature of Chinese studies (the results are orally presented with the current SLSR study together in Asia Pacific Stroke Conference, Hong Kong, September 2013; the full article is submitted for journal publication), we have demonstrated that survival time CI indicates confidence interval; HR, hazard ratio; SED, socioeconomic deprivation; and SLSR, South London Stroke Register. *The number of patients at the follow-up time was derived from those who were actually followed up to the time, including deaths.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%